Artificial intelligence in Ethiopian school curriculum: Educators' practices, challenges, and recommendations - Fitsum Gizachew Deriba; Ismaila Temitayo Sanusi (Computers and Education Open)
In light of the ongoing discourse on integrating artificial intelligence (AI) into formal education systems, it is imperative to examine both curriculum and teaching practices, particularly in developing regions. This study explores the Information Communication and Technology (ICT) curriculum of Ethiopian secondary schools to identify AI-related content within the learning guide. Additionally, it assesses ICT educators' knowledge, practices, challenges, and recommendations for effectively implementing AI in Ethiopian schools. Employing a qualitative approach, this study reviewed AI content in the Ethiopian secondary school ICT curriculum and conducted audio-recorded interviews with 10 ICT teachers. Document analysis and thematic analysis were utilized to interpret the collected data. The AI content in the curriculum was analyzed and findings were discussed within the framework of the Five Big Ideas in AI. Our findings reveal that the AI content in the Ethiopian secondary school ICT curriculum is predominantly definitional. The thematic analysis of teacher interview data highlights the methods employed in teaching AI, including pedagogical challenges such as limited understanding of AI concepts. Furthermore, several recommendations emerged for the effective implementation of AI in schools, including curriculum revisions to incorporate AI topics in early childhood and primary education, as well as professional development opportunities. We also discuss the implications, limitations, and future research directions of this study.